2021
DOI: 10.1016/j.jds.2020.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of different formulations of nystatin in an experimental model of oral candidiasis in sialoadenectomized rats

Abstract: Background/purpose Oral candidiasis is the most common fungal infection of the oral cavity and has become a focus of attention in recent years because of its association with highly topical immunosuppressive conditions. The aims of this study were to determine the value of microbiological, clinical and histological parameters of Candida albicans colonisation of the dorsal tongue surface as indicators of disease severity, and to evaluate therapeutic response to different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…In our study, we used the antifungal nystatin in a positive control group as a comparison parameter because it is considered the most commonly used topical antifungal for the treatment of oral candidiasis (31). In another study used topical nystatin once daily, all animals showed partial remission of lesions after 5 days of treatment (32). In contrary, 69% of the animals showed total remission of the lesion after 5 days of treatment.…”
Section: Discussionmentioning
confidence: 98%
“…In our study, we used the antifungal nystatin in a positive control group as a comparison parameter because it is considered the most commonly used topical antifungal for the treatment of oral candidiasis (31). In another study used topical nystatin once daily, all animals showed partial remission of lesions after 5 days of treatment (32). In contrary, 69% of the animals showed total remission of the lesion after 5 days of treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, animal model experiments and clinical studies provide important data regarding the efficacies of probiotics. Several animal models of oral, gastrointestinal and vaginal candidiasis have been proposed for analyses of fungal immunity and anti-fungal therapies [11,17,18,[21][22][23][24][25][26][27]. These animal models have aided in elucidating molecular mechanisms related to candidiasis; they have also facilitated the evaluation of novel therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Nystatin is a polyene antifungal drug that is of particular interest because it exhibits remarkable action against a wide range of pathogenic and non-pathogenic yeast and fungi and it is used in severely immune compromised patients and neonates [ 33 , 34 , 35 ]. While different formulations of nystatin have been developed [ 36 ], the topical formulation of nystatin remains the most widespread in clinical use [ 37 ]. Amphotericin B deoxycholate has been the “gold standard” treatment for invasive fungal infections for over 50 years [ 31 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%